2004
DOI: 10.1007/s10740-005-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

The density of molten indium at temperatures up to 600 K

Abstract: The pycnometer method is used to study the density of liquid indium in the temperature range from the melting point to 580 K. The purity of investigated metal is higher than 99.9% by mass. The confidence error of the measurement results does not exceed 0.1%. The experimental results are compared with the previously obtained reference data on the density of molten indium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The measurements of Crawley 9 were performed in absolute pycnometers with low uncertainty and were considered as primary data. The measurements of Karamurzov 7 and Alchagirov et al, 8 performed in an areometer densimeter, and those of Fisher and Philips, 11 taken in bubble-pressure instruments, were also part of the primary dataset, together with the γ-ray measurements of Stankus 6 and of Schneider and Heymer. 10 Finally, the measurements of Chentsov, 12 performed in a sessile-drop instrument, were considered as secondary data, as they were much higher than the results of other workers and also showed quite a different temperature gradient.…”
Section: Data Compilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements of Crawley 9 were performed in absolute pycnometers with low uncertainty and were considered as primary data. The measurements of Karamurzov 7 and Alchagirov et al, 8 performed in an areometer densimeter, and those of Fisher and Philips, 11 taken in bubble-pressure instruments, were also part of the primary dataset, together with the γ-ray measurements of Stankus 6 and of Schneider and Heymer. 10 Finally, the measurements of Chentsov, 12 performed in a sessile-drop instrument, were considered as secondary data, as they were much higher than the results of other workers and also showed quite a different temperature gradient.…”
Section: Data Compilationmentioning
confidence: 99%
“…(iv) Indium: 11 investigators reported measurements of the density of indium. The measurements of Alchagirov et al 8 and Crawley 9 were performed in absolute pycnometers and with very low uncertainty and were thus considered as primary data. The measurements of Stankus and Tyagel'sky 24 and Schneider and Heymer, 10 performed in a γray instrument with very low uncertainty, were also part of the primary dataset.…”
Section: Data Compilationmentioning
confidence: 99%
“…where C Bi(In) is the concentration of Bi in In for the growth of InSbBi and C Bi(Ga) is that in Ga melt during the growth of GaSbBi. Densities of indium [21] and gallium [18] at selected equilibrium temperatures were obtained using ρ In = 7.330 − 0.737…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…where C N(Bi) and C N(In) are the nitrogen concentrations in Bi and In melts, respectively, for the growth of InAsN and C N(Ga) is the nitrogen concentration for the growth of GaAsN from the Ga melt. Densities of Bi and In at the corresponding equilibrium temperatures required in the calculations were obtained using standard relations [16,17]. The density of Ga at the corresponding equilibrium temperatures was obtained using the relation [18] ρ = 6.32723 − 7.3743 × 10 −4 T + 1.37767 × 10 −7 T 2 (10) where T is in Kelvin and ρ is in (gm cm −3 ).…”
Section: Kinetics Of Growthmentioning
confidence: 99%